“Pro Peccatis Patrum Puniri”: A Moral and Legal Problem of the Inquisition - Pennington, Kenneth (Church history, 1978)
The first letter in Pope Innocent III's register of his second year was Vergentis in senium, a letter which he sent to the city of Viterbo in March, 1199. The decretal reflected Innocent's growing concern with heresy in the papal states and established new and more stringent penalties for those who rejected or subverted the Christian faith. In Vergentis, perhaps following the Roman lawyer Placentinus, Innocent imposed the traditional spiritual punishment of excommunication on heretics, equated heresy with lese majesty, and applied to convicted heretics the sanctions for treason in Roman law: complete confiscation of goods, even disinheriting innocent children. The punishment was fitting, Innocent observed, because a heretic injured celestial majesty, a crime far more heinous than any offense committed against temporal authority. Since the heretics in Viterbo continued to demand his attention later in his pontificate, we do not know how effective Innocent's decree was, but Vergentis did establish a precedent for papal action throughout Christendom. In order to root out all vestiges of heresy, Innocent extended the provisions of the decretal from the heretics themselves to their “supporters, defenders, and harborers.” The decretal marked the first firm step of his increasingly grim policy to use all of the resources of the church to extirpate heresy from Christian lands. The step from Viterbo to the Albigensian crusade was a short one. And, since heresy was an ecclesiastical crime, both laymen and clerics who were accused of heresy had their cases heard in ecclesiastical courts, giving lawyers another item to add to the list of cases in which the pope could exercise jurisdiction in the secular world.